Revealing learner beliefs in EFL learning across cultures and technologies - Hesmatantya, Vega (JEES (Journal of English Educators Society), 2025)
Learners' beliefs are a crucial factor in English as a Foreign Language (EFL) learning, as they influence motivation, learning strategies, and learning outcomes. Recent studies have shown that positive beliefs, such as confidence in one's own language abilities, promotes active participation and achievement, while negative beliefs can hinder progress. Sociocultural factors, prior learning experiences, and environmental context also play a significant role in shaping these beliefs. This study reviews empirical literature published in Scopus-indexed journals between 2020 and 2025 to examine the development of learners' beliefs within cross-cultural contexts and the integration of technology. The review reveals that learners' beliefs are related to their learning strategies, motivation, and learning orientation, and are influenced by social norms, cultural background, and pedagogies practices. Furthermore, technology integration, particularly through AI-based applications, gamified environments, and adaptive learning platforms, has been found to enhance positive beliefs by providing personalized materials, instant feedback, and interactive learning experiences. However, challenges such as limited digital infrastructure, unequal internet access, and insufficient teacher preparedness remain significant barriers, particularly in the Indonesian context. These findings underscore the need for adaptive and context-sensitive pedagogical strategies that can positively shape learners' beliefs, foster comprehensive language competencies, and effectively utilize technology to support inclusive and holistic EFL learning. Theoretically, this study contributes to deeper understanding of learners' beliefs in EFL contexts, while practically, it offers valuable insights for educators and curriculum developers in designing culturally responsive and technological integrated learning environments.